Potential Environmental Benefits of Ultralight Particleboards with Biobased Foam Cores - Christelle Ganne-Chédeville; Stefan Diederichs (International Journal of Polymer Science)
A new generation of ultralight particleboards (ULPB) with an expanded foam core layer produced in an in-line foaming step is under development. The environmental impacts of three types of ULPB containing foam based on 100% polylactic acid (PLA), 100% expanded polystyrene, and 50% PLA/50% polymethyl methacrylate, as well as a conventional particleboard (PB), have been compared in an LCA. Two approaches were chosen for the assessment: first, the “EPD-approach” in accordance with EN 15804 for EPD of building materials and second, a holistic-approach which allows an expansion of the system boundaries in order to forecast the consequences of a broader replacement of PB with ULPB. The results show that most of the environmental impacts are related to raw materials and end-of-life stages. Both approaches show that the exchange of PB with ULPB with a foam core based on PLA leads to a reduction of greenhouse gas emissions. On the other hand, the PLA is responsible for higher ecotoxicity results in comparison to non-bio-based polymers mainly due to agricultural processes. Both approaches allowed the drafting of complementary advisories for environmental impact reduction addressed to the developers.